2007
DOI: 10.1039/b617599f
|View full text |Cite
|
Sign up to set email alerts
|

The binding of phosphonic acids at aluminium oxide surfaces and correlation with passivation of aluminium flake

Abstract: Measurements of adsorption isotherms of a series of thirteen mono- and di-phosphonic acids have shown that these bind strongly to the surface of high surface area aluminium trihydroxide. The incorporation of such phosphonates into a suspension of aluminium flake in an aqueous medium, modelling the continuous phase of a water-based paint, greatly suppresses the evolution of hydrogen. Whilst strong binding of the phosphonate to aluminium oxides is an essential criterion for good passivation, other factors such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Carboxylate linkages to TiO 2 are labile in organic solvents, as evidenced by the evolution of mixed monolayers from kinetically controlled to thermodynamically controlled compositions. Phosphonic acids adsorb more strongly than carboxylic acids to metal oxides. To investigate the influence of the surface-attachment interaction on the formation and compositional evolution of mixed monolayers, we prepared mixed monolayers of MHDA and HPA (Chart ). Monolayers were prepared from coadsorption solutions in THF with χ T ,soln of 0.1, 0.5, and 0.9.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carboxylate linkages to TiO 2 are labile in organic solvents, as evidenced by the evolution of mixed monolayers from kinetically controlled to thermodynamically controlled compositions. Phosphonic acids adsorb more strongly than carboxylic acids to metal oxides. To investigate the influence of the surface-attachment interaction on the formation and compositional evolution of mixed monolayers, we prepared mixed monolayers of MHDA and HPA (Chart ). Monolayers were prepared from coadsorption solutions in THF with χ T ,soln of 0.1, 0.5, and 0.9.…”
Section: Resultsmentioning
confidence: 99%
“…Phosphonic acids adsorb more strongly than carboxylic acids to metal oxides. [87][88][89] To investigate the influence of the surface-attachment interaction on the formation and compositional evolution of mixed monolayers, we prepared mixed monolayers of MHDA and HPA (Chart 1). Monolayers were prepared from coadsorption solutions in THF with χ T,soln of 0.1, 0.5, and 0.9.…”
Section: Resultsmentioning
confidence: 99%
“…Supporting Information is available: experimental methods associated with ligand exchange reactivity, attempted syntheses, a determination of maximum nanoparticle surface coverage and solubility studies; a table for comparing key stretching bands observed by FTIR spectroscopy; a table of important 13 C NMR and FTIR data for literature diacyl disulfides; and experimental spectra. Additional referenced cited within the Supporting Information [50–59] …”
Section: Supporting Informationmentioning
confidence: 99%
“…This behavior distinguishes them from the corresponding aminocarboxylates, which exhibit much weaker interactions with mineral surfaces, especially near neutral pH. Some of the investigated adsorbents for phosphonates are calcite, clays, aluminum oxides, iron oxides, zinc oxide, hydroxoapatite, and barite. For all those compounds very strong adsorption is observed in the pH range of natural waters. On the other hand, in the case of the presence of metal ions such as Fe(III), Zn(II), or Cu(II), strong adsorption of the uncomplexed phosphonates, which resulted in a dissociation of the complexes on metal ions and the phosphonates, was discovered.…”
Section: Introductionmentioning
confidence: 99%